2004
DOI: 10.1074/mcp.m400002-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Arginine Adducts on Glyoxal-modified Ribonuclease

Abstract: Accumulation of advanced glycation end-products (AGEs) on proteins is associated with the development of diabetic complications. Although the overall extent of modification of protein by AGEs is limited, localization of these modifications at a few critical sites might have a significant effect on protein structure and function. In the present study, we describe the sites of modification of RNase by glyoxal under physiological conditions. Arg 39 and Arg 85 , which are closest to the active site of the enzyme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 24 publications
4
52
0
Order By: Relevance
“…S2) was compiled and used for MS and MS/MS data-driven database searching. Some of these amino acid modifications have already been detected in milk proteins [2][3][4][5]13,15,17,19,20]; others have been identified in other model proteins/peptides after their heating in the presence of sugars and/or sugar oxidation products [8][9][10]15,[29][30][31][32][33][34][35][36][37][38].…”
Section: Resultsmentioning
confidence: 96%
“…S2) was compiled and used for MS and MS/MS data-driven database searching. Some of these amino acid modifications have already been detected in milk proteins [2][3][4][5]13,15,17,19,20]; others have been identified in other model proteins/peptides after their heating in the presence of sugars and/or sugar oxidation products [8][9][10]15,[29][30][31][32][33][34][35][36][37][38].…”
Section: Resultsmentioning
confidence: 96%
“…We showed that a Glycer-AGE, which we identified to be hnRNPM, is a modified protein that was detected in cells exposed to high fructose concentrations, and this exposure induced a concentration-dependent increase in Glycer-AGEs (glyceraldehyde-modified . It is known that the ketones or aldehydes of sugars can modify the side chains of lysine and arginine residues in proteins [24,25] ; Cotham et al [26] demonstrated that dicarbonyl compounds react primarily with arginine residues. Lysine and arginine, amino acids that have a basic side chain, are important in RNA-protein interactions [27][28][29][30][31] .…”
Section: Cellsmentioning
confidence: 99%
“…27.5b) (Glomb and Lang, 2001). Dihydroxyimidazolidine adducts have been recently recognized as the primary products of modification of RNase A by GO, Arg39, and Arg85 (which are closest to the active site of the enzyme) being the primary sites of modification (Cotham et al, 2004). The dicarbonyl structure of GO makes it able to react with two Lys residues to form protein imidazolium cross-links (i.e., the GO-Lys dimer, GOLD) and imidazole cross-links (i.e., the GO-Lys-Arg dimer, GODIC) (Wells-Knecht et al, 1995;Lederer and Klaiber, 1999) (Fig.…”
Section: Glyoxal (Go)mentioning
confidence: 99%